Wave and symbol synchronizers - Reis, António D. (2005)
In this paper we present four wave synchronizers and four symbol synchronizers: analog, hybrid, combinational and sequential. All them are of the class closed loop. The wave synchronizers are vacated to synchronize withwaves or signals with deterministic phase/transition. The symbol synchronizers are vacated to synchronize withsymbols or signals with random phase/transition. The main objective is to study and compare the performance of the different wave and symbol synchronizers.